ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PERUSAHAAN - Beta Asteria; Selamat Riauwanto (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2022)
This study aims to analyze the effect of Leverage and Profitability on Cash Holding Companies listed on the Indonesia Stock Exchange. The sample of this study was 45 companies that were included in the Blue Chip stock category, in 2018. The data was carried out using regression analysis, through t test, F test and Coefficient of determination test. The results of the t test show that partially proven to have a significant effect on Cash Holding Company is Leverage, while partially profitability is not proven to have a significant effect on Cash Holding’s Company. Based on the F test, it is proven that Leverage and Profitability simultaneously have a significant effect on the Company Cash Holding. The coefficient of determination test obtained R2 results of 0.218, meaning that the leverage and profitability variables were able to explain the variability of Cash Holding of 21.80%. The remaining 78.20 was explained by other variables outside the model.